Organization of Distance Education in the System of Teacher Postgraduate Education - KASHYNA, GANNA; NIKOLAIEV, KYRYLO (Journal of Education, Technology and Computer Science, 2016)
The process of development, theoretical substantiation and implementation of distance educationsystem organization model into teacher postgraduate education has been considered in the paper.Postgraduate pedagogical study with wide-area distance study is greatly distinguished frompresent system by level of study quality, number of users, focus on personality, democracy, variance,application of modern information-communication technologies and telecommunicationnetworks in study. The platform of distance education has to be applied for supplement and expansionof traditional process of institution study and communication in the teacher postgraduateeducation institutes. Implementation of distance education in the teacher postgraduate educationsystem creates the educational system of retraining and professional development for teachers onthe-job, and improvement of educational services, proposed by educational institution.